2009
DOI: 10.1108/09526860910964843
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare quality and moderators of patient satisfaction: testing for causality

Abstract: The model has been found to capture attributes that characterize healthcare quality in a developing country and could represent other modern healthcare systems. Also, it can be used to evaluate other healthcare practices from patients' viewpoints. The study highlights the importance of healthcare quality as patient satisfaction predictors by capturing other effects such as patient status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 118 publications
(144 reference statements)
5
92
1
5
Order By: Relevance
“…While others incorporated satisfaction into their survey instrument by asking participants directly to reveal their satisfaction with care for each item that represented healthcare quality (Badri et al, 2009). Woodside et al (1989) identified other primary patient satisfaction determinants: Admissions; Discharge; Nursing care; Food; Housekeeping; and.…”
Section: Patient Satisfactionmentioning
confidence: 99%
“…While others incorporated satisfaction into their survey instrument by asking participants directly to reveal their satisfaction with care for each item that represented healthcare quality (Badri et al, 2009). Woodside et al (1989) identified other primary patient satisfaction determinants: Admissions; Discharge; Nursing care; Food; Housekeeping; and.…”
Section: Patient Satisfactionmentioning
confidence: 99%
“…Furthermore, perceived health care quality has a positive influence on patient satisfaction (Badri et al, 2009;Navid et al, 2010;Mpinganjira, 2011). Satisfaction meanwhile positively affects patient intentional behavior (Bendall-Lyon & Powers, 2004;Otani & Harris, 2004;Elluech, 2008).…”
Section: Hypotheses H1-h3mentioning
confidence: 99%
“…The researchers also noted that HOSPIQUAL affects the patients satisfaction of public and private health care services in Kuala Lumpur and Johore, Malaysia. Research in UAE revealed that perceived health care quality has a positive influence on patient satisfaction (Badri, Attia, & Ustadi, 2009). Navid, Ahmad Fuad and Yuserrie (2010) who conducted a research among the international patients who received treatement in Penang private hospitals in Malaysia concluded that all service quality dimensions have a positive relationship with customer satisfaction except for tangible dimension.…”
Section: Linking Service Quality Satisfaction and Behavioral Intentmentioning
confidence: 99%
“…Atliekant pačius pirmuosius pacientų pasitenkinimo tyrimus, dažnai jie būna netikslūs ir neatspindė-davo tikrųjų sveikatos priežiūros kokybės problemų [22]. Pacientų pasitenkinimo ar lūkesčių pateisinimo sveikatos priežiūros paslaugomis klausimynai dar buvo kritikuojami už jų trūkumą atskirti gerą ir blogą sveikatos priežiūrą, kadangi pacientų nebuvo klausiama apie jų pasitenkinimą jų gydymu [3].…”
Section: įVadasunclassified